Organochlorine insecticides level detected in water and sediments from the Langat River and a Lake near to a golf course at Bangi, Selangor - Lee , Yook Heng; Mazlin Mokhtar; Siti Rohaya Omar (Universiti Kebangsaan Malaysia, 2006)
The possible presence of 10 organochlorine insecticides (aldrin, heptachlor, lindane, endosulfan, p,p’-DDE, p,p-DDT, methoxychlor, chlordane, endrin and dieldrin) in the sediment and water of a lake and river that flow through the Kelab Danau UKM were examined. Altogether six sampling sites were surveyed and three samplings within a period of three months were carried out in 2001. The insecticides were analysed by using gas chromatography equipped with an electron capture detector. The results showed that endrin, chlordane and aldrin were present in all water samples with concentrations for endrin: 0.02-0.21 µg/L, chlordane: 0.05-0.16 µg/L and aldrin: 0.03-0.13 µg/L. Lindane and heptachlor were rarely detected in the water samples. For sediment, lindane, endrin and heptachlor were detected in all sediment samples. Their levels in sediments were 0.28-0.53 µg/kg for lindane, 0.06-0.53 µg/kg for heptachlor and 1.06-2.06 µg/kg for endrin. Insecticides such as p,p' -DDE, p,p-DDT, methoxychlor, endosulfan and dieldrin were not detected in sediments or water during most samplings. The presence of organochlorine insecticides in the aquatic environment of the golf club area may be attributed to the input from usage. Another source would be from the river upstream outside the golf club flow through an area of oil palm plantation, where these insecticides might have been used for pest control in the past.